The Impact of Corporate Governance and Supply Chain Management on the Accounting and Auditing Environment - Maytham Hazim Azeez Khuzaae; Zina Adnan Kareem Almihna; Alaa Awad Kadhim Al-bdairi (International Journal of Supply Chain Management, 2019)
Abstract- The purpose of this study is to investigate the effect of Corporate Governance and Supply Chain Management on the Accounting and Auditing Environment. The spatial scope of the research includes companies which are admitted to the Tehran Stock Exchange. This research is based on objective, applied and descriptive method, and the realm of time is between 2011 and 2016. Research includes two independent variables (supply chain management and corporate governance), two dependent variable (accounting and auditing environment), and control variables. Information is collected in both library and field. Assumptions were tested through linear regression. The results of the test showed that corporate governance and supply chain management affects the accounting and auditing environment. Keywords: Auditing Environment, Corporate Governance, supply chain management, Accounting, Tehran Stock Exchange.